2017
DOI: 10.1111/epi.13919
|View full text |Cite
|
Sign up to set email alerts
|

Epileptogenic networks in nodular heterotopia: A stereoelectroencephalography study

Abstract: This is the first quantitative SEEG study providing insight into the mechanisms generating seizures in nodular heterotopia. We demonstrate that both the heterotopic lesion and particularly the normotopic cortex are involved in the epileptogenic network. This could open new perspectives on multitarget treatments, other than resective surgery, aimed at modifying the epileptic network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
97
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 69 publications
(103 citation statements)
references
References 39 publications
5
97
1
Order By: Relevance
“…Insular epilepsy in patient 2. (A) SEEG recordings of entry or target cortex in one seizure episode, including insular cortex, opercular cortex, mesial frontal cortex (SMA and ACC) and OFC; (B) EI map of the same seizure event presents the increased ER at the ictal onset (from blue to yellow scale) and the detection parameters (circle, alarm time; cross, detection time) 15,16 in each chosen channel. The map showed that the middle and posterior insular short gyri were highly epileptogenic; (C) mean highest EI value of insular cortex, operculum and SMA in two seizure episodes; (D) frequency-specific (40-180 Hz) epileptogenicity maps were used here to show the cortical distribution of high frequency oscillation at the seizure onset (the map here was used to show the involvement of insular and opercular cortex in the present case, with mean T score (color scale) in two seizure episodes.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Insular epilepsy in patient 2. (A) SEEG recordings of entry or target cortex in one seizure episode, including insular cortex, opercular cortex, mesial frontal cortex (SMA and ACC) and OFC; (B) EI map of the same seizure event presents the increased ER at the ictal onset (from blue to yellow scale) and the detection parameters (circle, alarm time; cross, detection time) 15,16 in each chosen channel. The map showed that the middle and posterior insular short gyri were highly epileptogenic; (C) mean highest EI value of insular cortex, operculum and SMA in two seizure episodes; (D) frequency-specific (40-180 Hz) epileptogenicity maps were used here to show the cortical distribution of high frequency oscillation at the seizure onset (the map here was used to show the involvement of insular and opercular cortex in the present case, with mean T score (color scale) in two seizure episodes.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, the present PET analysis showed that the ventral rolandic cortex was significantly hypometabolic in patients with insulo-opercular epilepsy, which is of interest given the tendency to observe facio-cervical ictal motor signs. We also observed 15,16 in each chosen channel. The map showed that PSG, ALG, PLG and posterior central operculum were highly epileptogenic; (C) mean highest EI value of insular cortex, operculum, and SMA in two seizure episodes; (D) frequency-specific (80-200 Hz) epileptogenicity maps were used here to show the cortical distribution of high-frequency oscillation at the seizure onset (the map here was used to show the involvement of the insular and opercular cortex in the present case, with mean T score (color scale) in two seizure episodes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations